Comparative Analysis of the Financial Performance of Companies in The Cosmetics Sub Sector and Household Needs During and After the Covid-19 Pandemic in Indonesia and Thailand - Dewi, Widyana Purnama; Luayyi, Sri (Kirana Publisher (KNPub), 2024)
This study aims to analyze the comparative financial performance of cosmetics and household needs sub-sector companies during and after the covid-19 pandemic on the Indonesia Stock Exchange (IDX) and the Stock Exchange of Thailand (SET) in 2020 and 2023. Financial ratio variables are proxied by ROA, CR, TATO and DER. The object of research on the Stock Exchange of Thailand (SET) is a novelty in this research. The sampling technique in this study used purposive sampling method. The final sample obtained was 12 companies in the household cosmetics sub-sector on the Indonesia Stock Exchange (IDX) and the Stock Exchange of Thailand (SET) in 2020 and 2023. This study uses secondary data obtained through the official websites of the IDX and SET and related companies. This research is a comparative study with the Paired Sample T-Test and Wilcoxon Signed Ranks Test data analysis methods using SPSS version 25. The results showed that in Indonesia there were differences in TATO during and after the covid-19 pandemic, but ROA, CR, and DER had no differences. In Thailand, ROA, CR, TATO and DER did not experience differences during and after the covid-19 pandemic. Indonesia shows better financial performance compared to Thailand.